Revolutionary approach to risk assessment utilization of oxidized agricultural waste as inexpensive adsorbents in tannery effluent: a kinetic investigation - Elsayed, Hamed; Tohamy, Hebat-Allah S.; El-Sakhawy, Mohamed; El-Khateeb, M. A.; Nashy, El-Shahat H. A. (Environmental monitoring and assessment, 2025)
The production of leather requires extensive water usage, resulting in serious liquid waste, as leather tannery wastewater (LTW) is often discharged directly into the environment. Releasing polluted LTW straight into the environment leads to the buildup of many harmful substances, like heavy metals, dyes, dirt, chemicals, and oils, which can be dangerous for the environment and human health. Among effective wastewater treatments, adsorption is a recognized method capable of treating a diverse array of contaminants in wastewater. Among the novel and new adsorption substrates employed, dialdehyde Shellac (DAS) and dialdehyde Cellulose (DAC) have consistently demonstrated exceptional performance. This study aimed to improve the efficiency of TW treatment by using new oxidized natural byproducts to create dialdehyde compounds, DAS and DAC, and to investigate these compounds. Oxidation increases the by-product’s functional active sites and groups, making it easier to absorb heavy metals and toxic chemicals from tannery effluent. DAS evaluation shows high-quality treated effluent; the residual COD, BOD, and TSS were 225, 119, and 30 mg/L which represent 95.51%, 98.11%, and 98.82% removal rates, respectively. The most unpleasant element, chromium, was eliminated at a rate of 98.92%, dropping from 280 to 3 mg/L. DAC had residual COD, BOD, and TSS values of 380, 985, and 90 mg/L (80.1%, 84.36%, and 96.42% removal), respectively. The pseudo-second order model suited the adsorption data better than the pseudo-first order model for all samples, with R 2 values between 1.0 and 0.999. The Elovich equation better fits adsorption, with R 2 values between 0.936 and 0.965. The Freundlich isotherm model matches adsorption data better than other isotherm models due to its higher coefficient of determination. This study suggests modifying natural wastes to improve industrial wastewater absorption while being cheap and sustainable. By comparing our work to the literature on TW, we are able to draw out areas that may be the subject of future research and highlight areas that require additional examination. Graphical Abstract